Razlike v strukturi gibalnih sposobnosti nekdanjega perspektivnega smučarskega skakalca, danes vrhunskega kolesarja - Jošt, Bojan (Šport (Ljubljana), 2018)
The aim of the study was to establish the differences in the motor ability profile of a person who was considered a promising ski jumper a few years ago and is now a top cyclist. He quickly made progress in his ski-jumping career and, at the age of 16, he became one of the most talented Slovenian ski jumpers. At the Nordic Junior World Ski Championships he won a medal twice in team competitions. As a junior athlete he won three competitions in the FIS Continental Cup. Unfortunately, a severe fall on the ski-jump on 22 March 2007 prematurely ended the ski-jumping career of the then minor athlete. At 22, his big desire for sport activity brought him into cycling which appears to be completely different from ski jumping. Following a few years% training, he succeeded in joining the top professional cyclists. In the last two seasons he scored top results in this endurance sport, including a silver medal at the 2017 World Championship in time trial. At the end of his ski-jumping career in 2010, he was well prepared in terms of basic motor abilities and he had an excellent morphological profile. Besides typically ski-jumping abilities, he also had a high endurance component of power which surely eased his transition to top cycling. After seven years of strenuous training and cycling competitions, his final score of potential competitive performance in ski jumping significantly decreased. The largest decline was established in the tests of dynamic jumping power and movement coordination, which are important measurement instruments in ski jumping. He was still able to achieve high level of repetitive power of legs and abdominal muscles. As regards balance, flexibility and movement speed he has preserved a high level of movement potential, which can be of great benefit to him when developing cycling technical skills, especially in the technique of riding in difficult, new and unexpected conditions.
Keywords: gibalne sposobnosti; kolesarji; morfološki profil; motorični profil; smučarski skakalci